(untitled) ("Journal "U". Economy. Management. Finance.", 2022)
Today, the development prospects of any country directly depend on its scientific and technological progress. This axiom also applies to Russia, and the most important role in this is played by venture capital investment. In the modern world, it is one of the main sources of innovation financing. In this paper I will look at the role of venture capital funds in the Russian economy; I will consider the mechanism of venture capital funds; I will focus on the criteria that a venture capital fund uses when choosing a startup to invest material funds; and I will also consider the situation of the venture capital market during the sanctions